USING PICTURES TO IMPROVE STUDENTS COMPREHENSION OF DESCRIPTIVE TEXT TO THE SECOND YEAR STUDENTS OF SMP NEGERI 6 MANADO - H. N. Wajong, Samantha; T, Olii, Sanerita; Rombepajung, Paula (English Education Department, 2020)
The purpose of this study is to investigate whether the use of images can improve students reading comprehension of descriptive text This study was conducted at SMP Negeri 6 Manado This study was quantitative study with one group pre test and post test as the design The teaching method used for treatment was images The population of this study consisted of 7 classes in the second grade and the sample of this study consisted of VIII and 25 students They analyzed statistically taking into account the average score of the test The results of this study showed that the post examination score was higher than the pre examination The average score for the post test T2 is 8 52 and the average score for the pre test T1 is 5 This shows that the use of diagrams improves the student s comprehension of the explanatory text The results of can conclude that it is effective to use figures when teaching explanatory texts < p>